Odpowiedzi

2010-02-08T07:58:22+01:00
A) 2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x=-7y+42 /:7
23y=11x-32

x=-y+6
23y=11(-y+6)-32

x=-y+6
23y=-11y+34

x=-y+6
34y=34 /:34

x=-y+6
y=1

x=5
y=1


b) 10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15=x-5
25y+50+3x-15=-10

2x=-10y-10 /:2
25y=-3x-45

x=-5y-5
25y=-3(-5y-5)-45

x=-5y-5
25y=15y+15-45

x=-5y-5
25y=15y-30

x=-5y-5
10y=-30 /:10

x=-5y-5
y=-3

x=10
y=-3
1 1 1
2010-02-08T12:58:49+01:00
A)
2(2x-y)+3(x+3y)=42
5(x+3y)-8(2x-y)=-32

4x-2y+3x+9y=42
5x+15y-16x+8y=-32

7x+7y=42|:7
-11x+23y=-32

x=6-y
-11(6-y)+23y=-32
-66+11y+23y=-32
34y=34
y=1

x=6-1
x=5


b)
10(y+2)+3(x-5)=x-5
25(y+2)+3(x-5)=-10

10y+20+3x-15=x-5
25y+50+3x-15=-10

2x+10y=-10|:2
3x+25y=-45

x=-5-5y
3(-5-5y)+25y=-45
-15-15y+25y=-45
10y=-30
y=-3

x=-5-5*(-3)
x=-5+15
x=10